Nature of some Conceptual Problems in Geometry and in the Particle Dynamics (Global Journal of Science Frontier Research, 2017)
The particle dynamics conception (mathematical formalism) changes rather rare in the process of the particle dynamics development. It connected with associative delusions in the existing dynamics conception and with the logical reloading which is a means of the associative delusion overcoming. Influence of associative delusions (AD) onto development of physics and mathematics is investigated. The associative delusion (AD) means a mistake, appearing from incorrect associations, when a property of one object is attributed to another one. Examples of most ancient delusions are: (1) connection of the gravitation field direction with a preferred direction in space (instead of the direction to the Earth center), that had lead to the antipode paradox, (2) statement that the Earth (not the Sun) is a center of the planetary system, that had lead to the Ptolemaic doctrine. Now these ADs have been overcame.
Keywords: logical reloading; associative mistakes; structural approach; foundation of quantum theory; multivariant geometry; physics geomerization; investiga- t